Analisis Yuridis Penyalahgunaan Wewenang dalam Politik Hukum dan Tata Kelola Pemerintahan untuk Mencapai Tujuan Pemerintahan yang Efektif (Pusat Riset dan Inovasi Nasional, 2026)
The abuse of authority by public officials within Indonesia’s governmental administration has become an increasingly urgent issue to address. Such misconduct undermines the fundamental principles of good governance including transparency, accountability, and justice which are essential for ensuring efficient and effective government operations. This study aims to conduct an in-depth analysis of the forms of abuse of authority by public officials, the factors influencing such behavior, and its impact on the effectiveness of governance and public trust. The research employs a normative approach with a prescriptive legal method, analyzing legislation related to the abuse of authority as well as a case-based approach to explore the implementation of authority by public officials in governmental practice.The findings indicate that abuse of authority may occur in various forms, such as exceeding the limits of granted power, conflating different authorities, or acting arbitrarily for personal or group interests all of which contradict the principle of legality governing governmental actions. Moreover, such practices negatively affect the quality of public services and tarnish the image of governmental institutions. The study also finds that although Law No. 30 of 2014 on Government Administration provides a clear legal framework, its implementation remains hindered by weak internal and external oversight systems. Therefore, this research recommends strengthening more effective supervision mechanisms, enhancing transparency in administrative decision-making processes, and involving the public in monitoring efforts to ensure that public officials exercise their authority in accordance with established objectives in pursuit of a clean and just government.